English Podcast as Media for English Language Learning: A Case of Higher Education in the Pandemic Situation - Priyatmojo, Arif Suryo; Widhiyanto, Widhiyanto; Suprapti, Sri (Universitas Negeri Semarang, 2022)
The aim of the study was the implementation of English Podcast as the media for English language learning in higher education in the pandemic situation. The study used Research and Development Approach with the students of English department of UNNES as the subject of the study in three courses – Statistics, Intensive Listening and Functional Syntax. The procedure of doing the study consisted of introduction covering literature study and need survey; and development phases. The results produced a concept and a product of podcast based on literature study of books and national as well as international journal articles. Also, it shows that Podcast is very possible to be applied in higher education for its affordable infrastructures. The podcast is an Education Podcast using free-software application – Audacity with some supports such as Television, Portable Podcast Console, Desktop Podcasting Microphone Kit, Studio Headphone, dan Portable Computer [laptop]. The audio products were uploaded in the Podcast Website - https://anchor.fm/arif-suryopriyatmojo/episodes/. Suggestions for the study are the need of support from all stakeholders for podcast development that can reach broader community and 2) active participation of lecturers to integrate technology in the learning process.